Collaborative Governance Towards Development of Eco-Based Tourism Village in Kalipucang Village, Pasuruan Regency - Sulung Satriyo Irkham Pambudi; Agus Suryono; Endah Setyowati (Wacana Journal of Social and Humanity Studies, 2020)
This Research aims to explain the collaboration to develop eco-based tourism villages in Kalipucang Village, Pasuruan Regency. The research focus consists of three points such as collaborative governance process; collaborative governance results; and obstacle and supporting factors of collaborative governance in the development of eco-based tourism village in Kalipucang Village. Theoritically, collaborative governance theory and principles of ecotourism are used to analyse process and results of tourism village development. This research uses qualitative research methods and interactive data analysis technique models that include data condensation; data display; and verification and conclusion drawing. The results showed that the collaborative governance process was enforced by each stakeholders, but several obstacles happened among the procces, such as the lack role of the Pasuruan Regency government sector and internal conflict among village stakeholders. The results of collaborative governance show that the development of a tourism village has succeeded to establish 6 tourism destinations; homestays; an achievement from regency and provincial level; and benefits in the social, economic, environmental and political aspect. While the implementation of the whole principle of ecotourism only occurs in the tourism destinations of â€œOmah Kopiâ€ and â€œKampung Susuâ€.